Evaluation of a transitional care pharmacist intervention in a high-risk cardiovascular patient population. (1st September 2018) - Dempsey, Jillian; Gillis, Christine; Sibicky, Stephanie; Matta, Lina; MacRae, Calum; Kirshenbaum, James; Faxon, David; Churchill, William
Abstract: Purpose: The utility of a transitions-of-care (TOC) pharmacist intervention focused on improving the quality and safety of the medication process for high-risk cardiovascular patients was evaluated. Methods: A quality-improvement initiative was developed for patients with heart failure or acute coronary syndrome followed longitudinally at a hospital˴s outpatient cardiovascular clinic. The TOC pharmacist intervention occurred either before a patient˴s outpatient cardiovascular clinic appointment or during a hospitalization. The major outcome analyzed was the number of unplanned hospital readmissions within 30 days. Additional endpoints evaluated included the time to healthcare utilization, number of medication discrepancies identified, percentage of therapeutic recommendations accepted by a provider, number of medication access issues resolved, patient cost savings, patient satisfaction, and mean time spent on an intervention by the pharmacist per patient encounter. Results: A total of 118 patients received the TOC pharmacist intervention. A total of 516 medication discrepancies were identified and corrected, with 55.6% of discrepancies involving cardiovascular medications. A total of 244 recommendations for therapeutic optimization were provided, with an 81% provider acceptance rate and a 100% patient satisfaction rate. Fifty-five patients were provided with medication cost savings, and medication-access issues were resolved for 8 patients. A TOC pharmacist spent means of 98 and 73 minutes on patient education and coordination of care during inpatient and ambulatory encounters, respectively. The 30-day hospital readmission rate for patients with heart failure was reduced by 20%. Conclusion: A TOC pharmacist intervention improved the quality and safety of care across both inpatient and ambulatory settings for high-risk cardiovascular patients at our institution.